1992
DOI: 10.1128/aac.36.11.2481
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of SCE-2787 and related antibiotics in experimental animals

Abstract: The pharmacokinetic properties of SCE-2787 administered intravenously at a dose of 20 mg/kg of body weight were studied with mice, rats, rabbits, dogs, and monkeys and were compared with those of ceftazidime, cefpirome, and cefclidin in mice and dogs. The area under the concentration-time curve for plasma after intravenous administration was the largest in monkeys, followed by those in dogs, rabbits, rats, and mice, in that order. The elimination half-life ranged from 0.2 to 0.3 h in mice and rats to 0.7 to 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 8 publications
2
20
2
Order By: Relevance
“…The half-life values in plasma for both drugs were relatively short, as would be expected in mice, and within the same range. The half-life of ceftazidime as determined in this study was comparable to that found in other studies (32)(33)(34) and in our own laboratory in earlier experiments (35), although the half-life found by Fantin et al (32) was slightly longer. However, the pharmacokinetic analysis in the study reported here was far more extensive than in the previous analyses, and the concentration-time curves are reproducible and clearly dose proportional.…”
Section: Discussionsupporting
confidence: 75%
“…The half-life values in plasma for both drugs were relatively short, as would be expected in mice, and within the same range. The half-life of ceftazidime as determined in this study was comparable to that found in other studies (32)(33)(34) and in our own laboratory in earlier experiments (35), although the half-life found by Fantin et al (32) was slightly longer. However, the pharmacokinetic analysis in the study reported here was far more extensive than in the previous analyses, and the concentration-time curves are reproducible and clearly dose proportional.…”
Section: Discussionsupporting
confidence: 75%
“…Against the infection, cefpiramide was less effective than we had expected by the MIC than other antibiotics. The plasma half-life of cefpiramide after intravenous administration in mice is reported to be 11 min, which is comparable to those of other antibiotics, including cefozopran (12,15). However, the binding of cefpiramide to serum protein in mice is 44%, which is higher than that of cefozopran (7.1%) (12,15 3 after infection (8).…”
Section: Resultsmentioning
confidence: 82%
“…DISCUSSION Cefozopran, a new semisynthetic cephalosporin, showed a potent therapeutic effect against all infections used in this study. The pharmacokinetic profile of cefozopran is known to be similar to those of reference antibiotics used in this study, except for the protein-binding rate of cefpiramide in mouse serum (10,12,15).…”
Section: Resultsmentioning
confidence: 99%
“…To obtain blood, mice were sacrificed by bleeding from the axillary arteries and veins under ether anesthesia and plasma was obtained by centrifugation (3,000 ϫ g) of the blood sample. on May 10, 2018 by guest http://aac.asm.org/ modifications of the method described previously (14). There was no major detectable bioactive metabolite of TAK-456 in the mouse plasma.…”
Section: Methodsmentioning
confidence: 86%